The acts of King Arthur and his noble knights - Steinbeck, John, 1902-1968.; Horton, Chase; Malory, Thomas, Sir, 15th cent. (New York : Penguin Books, 2008)
Retells Sir Thomas Malory's tales of King Arthur and the brave Knights of the Round Table in twentieth-century language.
"First published in the United States of America by Farrar, Straus and Giroux 1976"--T.p. verso.
Retelling of Sir Thomas Malory's Le morte d'Arthur.
Horn Book.
School Library Journal.
Young Adult
Keywords: Arthur, -- King -- Fiction; Arthur, -- King -- Legends; Arthur, -- King -- Fiction; Britons -- Kings and rulers -- Fiction; Knights and knighthood -- Great Britain -- Fiction; Adventure stories; Arthurian romances; Historical fiction; Knights and knighthood -- Fiction; Great Britain -- Kings and rulers -- Fiction; Fantastic fiction; Fantastic fiction; Adventure stories; Arthurian romances; Historical fiction